Understanding the social dimension of sustainable agriculture : Swiss dairy farmers perspectives - Halter, Magdalena Margarita (SLU/Dept. of Energy and Technology, 2022)
The current food systems need to become more sustainable, and this involves the creation of balance between the economic, environmental and social dimension of these systems. The social dimension, however, is least clearly conceptualized and likely to be overlooked when the issues are not very obvious as this is the case for many regions in the global north. Switzerland, as a country in the global north, invests great sums of money to improve agricultures environmental performance and to secure public goods. But low income, the resulting precarious situations and financial pressure, long working hours and no holidays describe agriculture in Switzerland and especially the lives of farmers as well. By applying Q-Methodology, this study aims to identify key perspectives Swiss dairy farmers have about the social dimensions of sustainable agriculture. To gather statements, representing the understanding of the social dimension of sustainable agriculture by Swiss dairy farmers, two focus groups were conducted with the starting question: “What does the social dimension of sustainable farming mean to you?”. The data gathered during these focus groups was processed into 40 statements and these were sorted in forced distribution by 23 respondents, before a factor analysis was performed. This resulted in five perspectives representing 59.27% of the studies variance, from which four where interpretable into coherent perspectives and accordingly labelled. The “equality-perspective” is covering the most variance in this study and focuses on equal opportunities in agriculture and succession. The “passing on a successful business-perspective”, in contrast disagrees strongly with these equality statements while valuing statements regarding a successful business that can be passed on to the next generation high. The “family and friends-perspective” similarly desires a successful business but more importantly, is focused on the relations with family and friends. And the “education-perspective” agrees most with education related statements. Moreover, it was seen that the financial dimension can not be disconnected from the social discourse. Income was frequently discussed during the focus groups and the resulting statements were mostly agreed with by the sorting-exercise respondents. It was also seen that many of the perspectives disagreed with the same two statements which leads to the interpretation that the vanishing of farms and the ongoing rise of digitalisation in agriculture are not important social issues among the identified perspectives in this study.